PENGEMBANGAN MODUL IRISAN KERUCUT BERBANTUAN GEOGEBRA - Arta Ekayanti (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
The aim of this research was to develop a conic section modul. The modul used GeoGebra in presenting material. This research used development model of Plomp, with three step including preliminary research, prototyping stage and assesment phase. The result of validation test show that modul was valid because contents advisibility, presentation advisibility, graphic advisibility and language advisibility was stay on good level. Analysis of responses quetioner show that modul was practicable because presentation advisibility was in great level and material presenting advisibility and usefulness advisibility was in good level. In other hand, student test show that the modul was effective with score of classical completeness percent was 89.29%. Hence, modul developed satisfied aspect of quality namely valid, practise and effective.